Insertion of a mMoshan transposable element in PpLMI1, is associated with the absence or globose phenotype of extrafloral nectaries in peach [Prunus persica (L.) Batsch. Issue 1 (19th January 2022) - Lambert, Patrick; Confolent, Carole; Heurtevin, Laure; Dlalah, Naïma; Signoret, Véronique; Quilot-Turion, Bénédicte; Pascal, Thierry
Abstract: Most commercial peach [ Prunus persica (L.) Batsch] cultivars have leaves with extrafloral nectaries (EFNs). Breeders have selected this character over time, as they observed that the eglandular phenotype resulted in high susceptibility to peach powdery mildew, a major disease of peach trees. EFNs are controlled by a Mendelian locus ( E ), mapped on chromosome 7. However, the genetic factor underlying E was unknown. In order to address this point, we developed a mapping population of 833 individuals derived from the selfing of "Malo Konare", a Bulgarian peach cultivar, heterozygous for the trait. This progeny was used to investigate the E -locus region, along with additional resources including peach genomic resequencing data, and 271 individuals from various origins used for validation. High-resolution mapping delimited a 40.6 kbp interval including the E- locus and four genes. Moreover, three double-recombinants allowed identifying Prupe.7G121100, a LMI1-like homeodomain leucine zipper (HD-Zip) transcription factor, as a likely candidate for the trait. By comparing peach genomic resequencing data from individuals with contrasted phenotypes, a MITE-like transposable element of the hAT superfamily ( mMoshan ) was identified in the third exon of Prupe.7G121100 . It was associated with the absence or globose phenotype of EFNs. The insertion of the transposon was positively correlated with enhanced expression of Prupe.7G121100 . Furthermore, a PCR marker designed from the sequence-variants, allowed to properly assign the phenotypes of all the individuals studied. These findings provide valuable information on the genetic control of a trait poorly known so far although selected for a long time in peach.